PROFIT DISTRIBUTION MANAGEMENT PADA BANK SYARIAH - fitri, fitriyana; Adriyani, Komala; Sutrisno, Catur Ragil (IAIN Kudus, 2018)
This study aims to analyze the influence of the proportion of third party funds (DPK), operational cost to operating income (BOPO), financing to deposit ratio (FDR), bank size and capital adequacy ratio (CAR) to profit distribution management at Sharia Bank. The population is all Sharia Commercial Banks in Indonesia, the period of 2012-2015. Samples were taken using purposive sampling technique. The results show that third party funds (DPK), finance to deposit ratio (FDR) and bank size have no significant effect on profit distribution management (PDM). While BOPO and capital adequacy ratio (CAR) have a significant effect on profit distribution management (PDM).